The German intellectual quest for India - Rothermund, Dietmar (New Delhi : Manohar, 1986)
On the contribution of Matthias Christian Sprengel, 1746-1803, Friedrich von Schlegel, 1772-1829, and Friedrich Max Müller, 1823-1900, German Indologists, to Indological studies.
Includes index.
Keywords: Indologists -- Germany; India -- Civilization -- Study and teaching -- Germany